PENGGUNAAN STOCHASTIC SPREADSHEET UNTUK PENENTUAN WAKTU TANAM OPTIMUM KEDELAI DI BOAWAE, FLORES-NTTTHE USE STOCHASTIC SPREADSHEET FOR DETERMINATION OF OPTIMUM PLANTING TIME OF SOYBEAN OF BOAWAE, FLORES-NTT - W. Guntoro; Rizaldi Boer; Irsal Las; Ahmad Bey (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1999)
Abstract is available in the full text (pdf format)